Visualization of the Nucleolus Using Ethynyl Uridine - Dvořáčková, Martina; Fajkus, Jiří (Frontiers in Plant Science, 2018)
Thanks to recent innovative methodologies, key cellular processes such as replication or transcription can be visualized directly in situ in intact tissues. Many studies use so-called click iT chemistry where nascent DNA can be tracked by 5-ethynyl-2’-deoxyuridine (EdU), and nascent RNA by 5-ethynyl uridine (EU). While the labelling of replicating DNA by EdU has already been well established and further exploited in plants, the use of EU to reveal nascent RNA has not been developed to such an extent. In this article we present a protocol for labelling of nucleolar RNA transcripts using EU and show that EU effectively highlights the nucleolus. The method is advantageous, because the need to prepare transgenic plants expressing fluorescently-tagged nucleolar components when the nucleolus has to be visualized can be avoided